Ukrainian Research Schools Negative Thermal Factors at Workplaces - Yurii Strezhekurov; Anatolii Belikov (Challenges and Issues of Modern Science)
A very important issue in the context of the negative impact of excess thermal radiation on the health of people working in production. This is especially relevant in industries where there is a high risk of burns, overheating of the body and other thermal injuries.